CFD Simulation and Efficiency Analysis of Natural Gas Ejector-Booster System - Kurniawan, Aditya; Nuzuladzmi, Rafida Nariswari; Afni, Amanda Lailia Nur (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Natural gas production involving several gas-well streams with different operating pressure creates a problem, especially for lower-pressure streams. Usually, a compressor unit is installed to enable a lower-pressure stream to tie in the higher-pressure stream. However, this solution requires high costs and investment related to compressor operation. Natural gas ejector provides an alternative, where a higher-pressure stream act as the motive fluid to withdraw the lower-pressure stream.  This work aims to simulate the flow inside the ejector using ANSYS Fluent CFD simulator. The model used is validated to published data by other authors. Ejector efficiency is calculated for several operating pressure and ejector geometry: ratio of mixing tube length to diameter. We found that the variation in L/D ratio of mixing tube in current study did not significantly affect the ejector performance. Conversely, it was strongly affected by both motive and suction pressure, where the entrainment ratio is generally higher for lower pressure ratio. On the other hand, the efficiency of ejector process exhibited an optimum behavior, where we obtained the highest efficiency of 26.7% at pressure ratio of 0.1765. Therefore, this result can be utilized as the recommended operating condition.